LEGAL FOCUS: British Columbia's proposed optician's regulation - West, Alan (Canadian Journal of Optometry, 2021)
The Canadian Association of Optometrists sought legal counsel regarding the proposed opticians regulation in British Columbia. Of interest to members, the following letter by Alan West, dated July 13, 2004, provides a relevant legal perspective to the issue of increasing the permitted scope of practice of opticians.